Pengaruh Digitalisasi dan Daya Saing Industri Kecil dan Menengah (IKM) pada Peningkatan Pendapatan Kerajinan Cangkang Kerang di Wilayah Pesisir Surabaya - Eksel Perdian Anggara; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study applies a quantitative approach with a survey method as a data collection technique. Research data were obtained by distributing questionnaires to respondents who were the subjects of the study, namely small and medium enterprises (SMEs) engaged in shell craft in the coastal areas of Surabaya. The influence of digitalization and competitiveness on increasing income from digitalization was measured through the use of social media, e-commerce platforms, and the use of information technology in business activities. Meanwhile, the competitiveness variable was measured based on product quality, innovation, price, and marketing capabilities. Digitalization has a positive effect on increasing income for small and medium enterprises (SMEs) engaged in shell craft. The use of digital media has been proven to be able to expand the market and increase sales volume. In addition, competitiveness also affects income, where innovation is the main factor that drives increased sales value. Simultaneously, digitalization and competitiveness contribute significantly to increasing income for small and medium enterprises (SMEs). Support for related institutions and business actors in digital literacy, product innovation, and sustainable marketing strategies is needed to strengthen competitiveness and improve the welfare of coastal communities.